Closing the mathematics achievement gap: exploring the applicability of growth mindset in South Africa - Morse, Katherine (Department of Psychology, 2022)
Growth mindset interventions have been shown to give small but significant boosts to mathematics performance. These interventions are both brief and cheap, making them attractive for boosting mathematics performance. Is it possible that South African students can benefit from a growth mindset intervention? Mindset assessments and interventions have predominantly been developed in the United States. There have been applications of the assessments and interventions to other cultural contexts, often with minimal adaptions. Adaptions are not reported in detail (or thoroughly evaluated) in existing research literature. In a series of four studies, I establish that South African high school students do have mathematics mindsets akin to the fixed and growth mindsets reported elsewhere. Using an iterative design process and item analysis, I modified a mathematics mindset assessment for use with disadvantaged students in South Africa. In two correlational studies I established validity and reliability for a mindset assessment I call “Thinking About Maths”. I examined the contribution of mathematics mindsets to mathematics performance, in comparison with mathematics anxiety, study attitude and study milieu (or environment). I found that whilst mindsets do contribute to performance, the contribution is minimal compared to other variables measured. Additionally, I found that in an impoverished study environment males have high mathematics anxiety which inhibits mathematics performance whereas females have high study attitude, boosting mathematics performance. With assistance from students and teachers, I developed a mindset intervention that is culturally appropriate and relevant. 305 Grade 9 students participated in a field-based quasi-experiment, which had a passive control group. The intervention was delivered on WhatsApp over four weeks. Each week contained a growth mindset message, a YouTube clip, advice on a learning strategy, and an integration activity. The groups were facilitated by young adult mentors. It was clear that WhatsApp groups were an effective mode of delivery and there was good evidence of participation from students. Mathematics performance at the intervention school improved significantly beyond that of the control school. The strength of the intervention seems to lie in the combination of mindset messaging and the teaching of effective strategies.